Study the current scenario of hand foot mouth disease an Indian prospective - Sahota, Ravi; Kaur, Navpreet; Singh, Gurpal; Upadhyay, Nisha (International Journal of Contemporary Pediatrics, 2020)
Background: The hand-foot-mouth disease (HFMD) is an acute communicable disease, mostly affecting children under 5 years of age and caused by human enterovirus 71 (EV-A71) and coxsackievirus A16 (CV-A16). The usual incubation period is 3 to 7 days. Early symptoms are likely to be fever often followed by a sore throat followed by loss of appetite and general malaise. Aim and objectives was to study the trend of hand foot and mouth disease in a private hospital in Uttarakhand over 5 successive years. Methods: This cross-sectional study was carried among 297 cases of HFMD newborn screened at pediatrics department of Sahota Super-specialty hospital, Kashipur, Uttarakhand during year 2015 to 2019 after ethical clearance of institutional ethical committee. Diagnosis is coded with ICD-10. SPSS version 20 was used to calculate frequencies and percentiles. Results: Almost 29 cases of HMFD were picked in 2015, 32 cases in 2016, 43 cases in 2017, 81 cases in 2018, 112 in 2019. Fever observed in 86% cases. Neurological complications were observed in 9 (3%) cases, pneumonitis in 14 (4.7%) cases, cardiomyopathy observed in 3 (<1%) case. One death was reported. Conclusions: It is vital to screen patients with HFMD for these abnormal clinical presentations, allowing timely initiation of appropriate interventions to reduce the mortality. Increased awareness about vaccination in a developing nation like India and vaccination program at the grass root levels have eradicated certain lethal diseases.